The United States acid rain program: are tradable emission permits working efficiently? - Zeller, Todd D. (Kansas State University, 2009)
The report examines the extent to which the United States market for tradable pollution permits has been an efficient way to reduce sulfur dioxide emissions from coal-burning power plants. To do so, this report first provides background information on the effects of SO2 emissions on the environment in the United States. It discusses the initial attempt with the 1970 Clean Air Act to reduce these emissions and its degree of success. The details of the 1990 Amendments are then given. The economic theory behind the different methods of pollution control (quantity regulation, technology mandate, taxation, and emissions restriction through tradable permits) is explained and their efficiency regarding consumer and producer surplus is contrasted. The report then reviews published articles regarding the topic at hand. The U.S. Acid Rain Program has been found to be very efficient in its ability to reduce sulfur dioxide emissions at a low cost to the producers.
Keywords: SO2; acid rain; Clean Air Act; pollution control; Economics, General (0501)